Номер 53 гдз 8 класс алгебра Муравин Муравина

1)\begin{equation} \frac{b\left ( 9a-8b \right )^{2}+\left ( 3a-4b \right )^{3}}{27a^{2}}=a-b. \end{equation} \begin{equation}\frac{b\left ( 81a^{2}-144ab+64b^{2}+27a^{3}-108a^{2}b+144ab^{2}-64b^{3} \right )}{27a^{2}}= \end{equation} \begin{equation}=\frac{81a^{2}b-144ab^{2}+64b^{3}+27a^{3}-108a^{2}b+144ab^{2}-64b^{3}}{27a^{2}}= \end{equation} \begin{equation}=\frac{-27a^{2}b+27a^{3}}{27a^{2}}=\frac{27a^{2}\left ( a-b \right )}{27a^{2}}=a-b \end{equation} 2)\begin{equation}\frac{\left ( x+y \right )^{3}-y\left ( 3x+2y \right )^{2}}{3x^{2}}=\frac{x}{3}+y \end{equation} \begin{equation} \frac{x^{3}+3x^{2}y+3xy^{2}+y^{3}-y\left ( 9x^{2}+12xy+4y^{2} \right )}{3x^{2}}= \end{equation} \begin{equation}=\frac{x^{3}+3x^{2}y+3xy^{2}+y^{3}-9x^{2}y-12xy^{2}-4y^{3}}{3x^{2}}= \end{equation} \begin{equation}=\frac{x^{3}-9xy^{2}-3x^{2}y-4y^{3}}{3x^{2}}= \end{equation} \begin{equation}=\frac{-\left ( 8x^{3}+4y^{3} \right )-\left ( 9xy^{2}-3xy \right )}{3x^{2}}= \end{equation} \begin{equation}=\frac{x^{3}+3x^{2}y+3xy^{2}+y^{3}-9x^{2}y-12xy^{2}-4y^{3}}{3x^{2}}= \end{equation} \begin{equation}=\frac{x^{3}-3y^{3}-6x^{2}y-9xy^{2}}{3x^{2}} \end{equation}